Exploring the Experiences, Perceptions and Social Dynamics of Electronic Cigarette Users: A Qualitative Study - Ersan Gürsoy; Rıdvan Kaya (Wiley, 2024)
ABSTRACT Introduction Electronic cigarettes, or e‐cigarettes, are rapidly gaining popularity throughout the globe as safer alternatives to traditional cigarette smoking. There are significant public health concerns due to the uncertainty of long‐term health consequences. This study aims to examine the experiences, attitudes and social dynamics of e‐cigarette users to provide guidance for public health policies and interventions. Methods In this qualitative descriptive study, semi‐structured interviews were conducted. Fifteen e‐cigarette users were recruited using a snowball sampling strategy, where initial participants referred other suitable users. All participants had at least 6 months of regular e‐cigarette use. Data were collected through face‐to‐face interviews with open‐ended questions. The interviews were transcribed verbatim and reviewed by the researchers. This review identified four main themes and eight sub‐themes. Results The four main themes identified as a result of the analysis are as follows: (1) initiation and usage experiences; (2) perceptions of health effects; (3) social and environmental factors and (4) addiction and future plans. Participants primarily began using e‐cigarettes out of curiosity, due to the appealing fragrance and the belief that they were less harmful than traditional cigarettes. Usage patterns varied among participants, with some reporting minimal cravings in the early morning hours. Opinions on the long‐term health effects of e‐cigarettes were diverse, with many participants acknowledging uncertainty. Peers and family members perceived e‐cigarettes as more socially acceptable than traditional smoking, resulting in fewer negative reactions. Finally, participants' levels of addiction and intentions to quit varied, with some expressing a desire to reduce or cease usage due to health concerns. Conclusion The findings of this study indicate that the adoption of e‐cigarettes is influenced by a confluence of factors, including curiosity, the perception of reduced damage in comparison to conventional cigarettes and social acceptance. Notwithstanding these claimed advantages, users have a diverse array of beliefs and understandings concerning the enduring health consequences of e‐cigarettes. The presence of varying levels of addiction and the corresponding aspirations to cease the behaviour highlight the necessity for focused public health interventions. Patient or Public Contribution E‐cigarette users were actively involved in this study, providing essential insights and feedback throughout. Their first‐hand experiences shaped the interview guide and contributed to the identification of key themes. Participants also reviewed and confirmed the accuracy of the interview transcripts, ensuring the reliability of the data.